Taṭbīq al-Wasīlah al-Raqmiyyah "Klāss Dūjū" bi Istikhdām Namūżaj "Flībīd Klāsrūm" li Taʿlīm al-Lughah al-ʿArabiyyah - Lubis, Chadijah Qubro; Huda, Miftahul; Munjiah, Ma'rifatul (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
Educational technology is a crucial tool for advancing the teaching-learning process, prompting researchers to explore supportive digital media. This study examined the impact of implementing the digital tool ClassDojo with the Flipped Classroom model in teaching Arabic to ninth-grade students at two schools in Medan. The research responded to the rising need to improve students’ Arabic skills and foster greater engagement in the learning process, especially amid shifts to technology-based models that support self-directed learning. This study employed a descriptive qualitative method to explore the experiences and perceptions of students and teachers regarding the implementation of ClassDojo using the Flipped Classroom model. Data were collected through interviews, observations, and documentation, as well as primary sources such as students and teachers and secondary sources such as previous studies and relevant literature. The researchers analyzed the data using statistical analysis tools and examined interview data to understand the impact of the Flipped Classroom model with ClassDojo on student learning. Results show that using ClassDojo in the Flipped Classroom model significantly improves students’ engagement and comprehension compared to traditional methods. This study highlights the value of integrating educational technology with innovative models like Flipped Classroom to enhance learning effectiveness and provide an interactive learning environment.